Human middle-latency auditory evoked potentials: vertex and temporal components. - Anthony T. Cacace; Satya-Murti, S.; Jonathan Wolpaw (Electroencephalography and clinical neurophysiology, 1990)
We recorded middle-latency (20-70 msec) auditory evoked potentials (MLAEPs) to monaural and binaural clicks in 30 normal adults (ages 20-49 years) at 32 scalp locations all referred to a balanced non-cephalic reference. Our goal was to define the MLAEP components that were present at comparable latencies and comparable locations across the subject population. Group and individual data were evaluated both as topographic maps and as MLAEPs at selected electrode locations. Three major components occurred between 20 and 70 msec, two well-known peaks centered at the vertex, and one previously undefined peak focused over the posterior temporal area. Pa is a 29 msec positive peak centered at the vertex and present with both monaural and binaural stimulation. Pb is a 53 msec positive peak also centered at the vertex but seen consistently only with binaural and right ear stimulation. TP41 is a 41 msec positive peak focused over both temporal areas. TP41 has not been identified in previous MLAEP studies that concentrated on central scalp locations and/or used active reference electrode sites such as ears or mastoids. Available topographic, intracranial, pharmacologic, and lesion studies indicate that Pa, Pb and TP41 are of neural origin. Whether Pa and/or Pb are produced in Heschl's gyrus, primary auditory cortex, remains unclear. TP41 is probably produced by auditory cortex on the posterior lateral surface of the temporal lobe. It should prove of considerable value in experimental and clinical evaluation of higher level auditory function in particular and of cortical function in general.
Keywords: (human); middle-latency auditory evoked potential (MLAEP); temporal components; vertex components